Functional analysis of eliciting plant response protein Epl1-Tas from Trichoderma asperellum ACCC30536 - Yu, Wenjing (Sci Rep, 2018)
Eliciting plant response protein (Epl) is a small Trichoderma secreted protein that acts as an elicitor to induce plant defense responses against pathogens. In the present study, the differential expression, promoter analysis, and phylogenetic tree analysis of Epl1-Tas (GenBank JN966996) from T. asperellum ACCC30536 were performed. The results showed Epl1-Tas could play an important role in the interaction between T. asperellum ACCC30536 and woody plant or woody plant pathogen. Furthermore, the effect of the Escherichia coli recombinant protein rEpl1-e and the Pichia pastoris recombinant protein rEpl1-p on Populus davidiana × P. alba var. pyramidalis (PdPap) was studied. In PdPap seedlings, rEpl1-e or rEpl1-p induction altered the expression levels of 11 genes in the salicylic acid (SA, three genes), jasmonic acid (JA, four genes) and auxin (four genes) signal transduction pathways, and five kinds of enzymes activities The induction level of rEpl1-p was significantly higher than that of rEpl1-e, indicating that rEpl1-p could be used for further induction experiment. Under 3 mg/mL rEpl1-p induction, the mean height of the PdPap seedlings increased by 57.65% and the mean lesion area on the PdPap seedlings leaves challenged with Alternaria alternata decreased by 91.22% compared with those of the control. Thus, elicitor Epl1-Tas could induce the woody plant resistance to pathogen.